Improving CMAS-corrosion resistance of YSZ-based thermal barrier coatings with Al2O3 addition - Han, Jiasen; Zou, Yong; Wu, Dongting; Chen, Ji; Zhang, Yongang (Surface & coatings technology, 2022)
Thermal barrier coatings (TBCs), exposed to the molten calcium‑magnesium‑aluminum-silicate (CMAS) deposits, could become degraded more readily during service. In this paper, the composite Al2O3/YSZ TBCs with different Al2O3 additions were prepared through the atmospheric plasma spraying technique and their resistance to CMAS corrosion at 1250 °C was carefully compared to the 7YSZ (7 wt.% Y2O3 stabilized ZrO2) TBCs. It was found that two distinct microstructural characteristics, i.e. thermo-chemical reaction zone and CMAS physical-infiltration zone, were identified for both the 7YSZ coating and the 10 wt.%Al2O3-7YSZ coating. The thermo-chemical reaction zone was severely corroded by molten CMAS, inducing the dissolution and re-precipitation of YSZ material and generating small globular m-ZrO2 particles. Furthermore, these two coatings were completely infiltrated (approximately 300 μm) and developed significant macroscopic bending. With the Al2O3 addition increasing above 20 wt.%, the depth of the thermo-chemical reaction zone was restricted to 35 μm without obvious CMAS physical-infiltration. During CMAS attacking the Al2O3/YSZ coating, continuous dissolution of Al2O3 into CMAS melt could promote anrthite crystallization along the CMAS-coating interface, which effectively restrained CMAS penetration and improved CMAS corrosion resistance. •The 300 μm thick 7YSZ coating was completely degraded by CMAS corrosion at 1250 °C for 5 h.•Al2O3 addition (above 20 wt.%) effectively arrested CMAS penetration and improved CMAS corrosion resistance.•Dissolution of Al2O3 from Al2O3/YSZ composite coating into CMAS melt promoted anorthite crystallization.